SOSIALISASI KESELAMATAN DAN KESEHATAN KERJA (K3) KEPADA STAF DAN PEKERJA PERUSAHAAN PT TEDJA JAYA KREASI DENPASAR - Made Yuyun Praptaningsih; Anak Agung Komang Suardana; Gde Indra Surya Diputra (UNHI Press, 2023)
Occupational Health and Safety (K3) is currently the main focus for all companies, especially those operating in the construction sector. The construction services sector is a sector that has a high risk of work accidents because it comes into direct contact with dangerous equipment and terrain. So this writing was carried out to introduce the importance of K3 in work methods. Socialization was carried out by visiting the project from the company PT Tedja Jaya Kreasi then socializing K3 to field supervisors and explaining the use of Personal Protective Equipment (PPE). From the socialization carried out on the implementation of K3 in the field, it is different in each project depending on the scale of the project, from interviews I conducted with field supervisors, the implementation of K3 has been implemented in all projects but inconsistently and there is a lack of socialization regarding work and work methods that prioritize safety at work.